2015
DOI: 10.1093/mutage/geu084
|View full text |Cite
|
Sign up to set email alerts
|

Rat Pig-a mutation assay responds to the genotoxic carcinogen ethyl carbamate but not the non-genotoxic carcinogen methyl carbamate

Abstract: Determination of the mode of action of carcinogenic agents is an important factor in risk assessment and regulatory practice. To assess the ability of the erythrocyte-based Pig-a mutation assay to discriminate between genotoxic and non-genotoxic modes of action, the mutagenic response of Sprague Dawley rats exposed to methyl carbamate (MC) or ethyl carbamate (EC) was investigated. EC, a potent carcinogen, is believed to induce DNA damage through the formation of a DNA-reactive epoxide group, whereas the closel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
9
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 30 publications
2
9
0
Order By: Relevance
“…It is noteworthy that EC caused a significant induction of Pig‐a mutant cells: increased RET CD59− and RBC CD59− frequencies were noted in both the 3‐day and 28‐day studies. The kinetics and magnitude of the mutant cell responses in the 3‐day and 28‐day studies were very similar to those shown in an experiment conducted by Labash et al () in male and female rodents exposed to 600 mg/kg/day EC for 3 consecutive days and the research of Bemis et al () in rats dosed orally for 28 consecutive days with 250 mg/kg/day EC. However, the maximal mutation frequency of RET in our 28‐day treatment study with EC (150–300 mg/kg/day), an ~13.2‐fold increase over the control, was lower than the ~74.0‐fold increase in a similar study conducted by Stankowski et al (), where SD rats were treated orally with 25–250 mg/kg/day using the same dosing protocol; while the maximal ~26.4‐fold increase over the control for mutant RBC in our study is greater than the ~8.1‐fold increase in the study of Stankowski et al ().…”
Section: Discussion and Summarysupporting
confidence: 86%
“…It is noteworthy that EC caused a significant induction of Pig‐a mutant cells: increased RET CD59− and RBC CD59− frequencies were noted in both the 3‐day and 28‐day studies. The kinetics and magnitude of the mutant cell responses in the 3‐day and 28‐day studies were very similar to those shown in an experiment conducted by Labash et al () in male and female rodents exposed to 600 mg/kg/day EC for 3 consecutive days and the research of Bemis et al () in rats dosed orally for 28 consecutive days with 250 mg/kg/day EC. However, the maximal mutation frequency of RET in our 28‐day treatment study with EC (150–300 mg/kg/day), an ~13.2‐fold increase over the control, was lower than the ~74.0‐fold increase in a similar study conducted by Stankowski et al (), where SD rats were treated orally with 25–250 mg/kg/day using the same dosing protocol; while the maximal ~26.4‐fold increase over the control for mutant RBC in our study is greater than the ~8.1‐fold increase in the study of Stankowski et al ().…”
Section: Discussion and Summarysupporting
confidence: 86%
“…Treatments were based on previous studies (11-13) with male rats that showed these dose levels are tolerated and significant increases in Pig-a mutant phenotype cells are induced.…”
Section: Methodsmentioning
confidence: 99%
“…The frequency of Pig-a mutant phenotype cells was monitored before, during, and after 28 consecutive days of oral gavage exposure to 0, 125, 250 or 500 mg MC/kg bw/day in male Sprague-Dawley rats (Bemis et al, 2015). Peripheral blood was collected on days −5 (i.e.…”
Section: Methyl Carbamatementioning
confidence: 99%
“…MC proved to be negative in several in vitro genotoxicity assays and in vivo in the SCE assay in mice (Cheng et al, 1981), the Pig A assay and in the peripheral blood micronucleated reticulocytes assay in rats (Bemis et al, 2015),. The Panel noted that, in contrast to the chemically related ethyl carbamate (urethane), the methyl group of MC does not readily undergo biotransformation to an epoxide.…”
Section: Methyl Carbamatementioning
confidence: 99%